2012
DOI: 10.1155/2012/341479
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Apoptosis and Cell Cycle Arrest in Human Colorectal Carcinoma by Litchi Seed Extract

Abstract: The Litchi (Litchi chinensis) fruit products possess rich amounts of flavanoids and proanthocyanidins. Its pericarp has been shown to inhibit breast and liver cancer cell growth. However, the anticolorectal cancer effect of Litchi seed extract has not yet been reported. In this study, the effects of polyphenol-rich Litchi seed ethanol extract (LCSP) on the proliferation, cell cycle, and apoptosis of two colorectal cancer cell lines Colo320DM and SW480 were examined. The results demonstrated that LCSP significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 28 publications
4
35
0
Order By: Relevance
“…Xiao and her coworkers proved that the Litchi medicated serum (water extract and granules) can significantly suppress the cells growth of S180 sarcoma and ehrlich ascites carcinoma (EAC) of mice in vivo and vitro [7], as well as the HepG 2 human liver cancer [8]. Hsu et al [9] discovered that the polyphenol-rich Litchi seed ethanol extract (LCSP) can significantly induce apoptotic cell death in a dose-dependent manner and arrest cell cycle in G2/M in colorectal carcinoma SW480 and Colo320DM cells. Similar water-soluble crude ethanolic extract in Litchi fruit pericarp also showed a dose-and time-dependent inhibitory effect on the growth of MCF-7 and MDA-MB-231 breast cancer cells where the maximal inhibition of cell growth (>80%) was obtained at 320 μg/ml with the IC50 80 μg/ml [10].…”
Section: Pharmacological Antitumor Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Xiao and her coworkers proved that the Litchi medicated serum (water extract and granules) can significantly suppress the cells growth of S180 sarcoma and ehrlich ascites carcinoma (EAC) of mice in vivo and vitro [7], as well as the HepG 2 human liver cancer [8]. Hsu et al [9] discovered that the polyphenol-rich Litchi seed ethanol extract (LCSP) can significantly induce apoptotic cell death in a dose-dependent manner and arrest cell cycle in G2/M in colorectal carcinoma SW480 and Colo320DM cells. Similar water-soluble crude ethanolic extract in Litchi fruit pericarp also showed a dose-and time-dependent inhibitory effect on the growth of MCF-7 and MDA-MB-231 breast cancer cells where the maximal inhibition of cell growth (>80%) was obtained at 320 μg/ml with the IC50 80 μg/ml [10].…”
Section: Pharmacological Antitumor Activitymentioning
confidence: 99%
“…Either reducing Bcl-2 protein or increasing the Bax protein can promote apoptosis of tumor cells, otherwise the tumor cell apoptosis will be restrained [17] [18]. Hsu et al [9] found that Litchi seed ethanol extract (LCSP) can increase the expression of Bax or reduce the expression of Bcl-2 to regulate the apoptosis genes of tumor cells and eventually promote the cell apoptosis.…”
Section: Hepg2mentioning
confidence: 99%
“…They are reported to possess anti-inflammatory, antiallergic, anti-flatulent, anti-diabetic, anti-hyperlipidemic, anti-platelet, anti-pyretic, anti-obesity, cardio-protective, anti-viral and anti-cancer effects (Kilari and Putta, 2016;Ibrahim and Mohamed, 2015;Islam et al, 2013;Patel et al, 2012;Zhao et al, 2007). They have been traditionally used to treat gastralgia, neuralgia, cough, hernia-like conditions, blood stasis in women and testicular swelling (Hsu et al, 2012). Litchi seed extract was found to inhibit degradation of collagen, elastin and hyaluronic acid, increase production of collagen in normal human fibroblasts and thus can be effectively used to maintain the tension and moisture of the skin, preventing wrinkles.…”
Section: Description Of Fruits and Spectrum Of Pharmacological Activimentioning
confidence: 99%
“…The caspase cascade is activated and expression of Fas protein is stimulated (Zhang and Zhang, 2015). Production and secretion of cytokines, epidermal growth factor (EGF), epidermal growth factor receptor (EGFR), platelet derived growth factor (PDGF) and tumor necrosis factor-α (TNF-α) and inflammatory factors, IL-1, TNF-α, IFN-γ is facilitated by litchi seed extract (Lin et al, 2013;Hsu et al, 2012).…”
Section: Mechanisms Of Anti-cancer Activity Litchimentioning
confidence: 99%
“…The supernatant was concentrated using a rotary evaporator under reduced pressure in a water bath at <35˚C and, then, freeze-dried. The final crude extract was defined as MSP, in which polyphenol species named total phenols, total flavonoids and condensed tannins were measured by colorimetry methods as previously described [15]. Briefly, the amount of total phenolics in MSP, estimated by the Folin-Ciocalteu method was performed by mixing the samples (0.25 mL) with 3.5 mL of distilled water in screw-capped test tubes followed by addition of 0.5 mL of Folin-Ciocalteu solution.…”
Section: Msp Preparationmentioning
confidence: 99%